Beware of Doping: Ta2O5 Nanotube Photocatalyst Using CNTs as Hard Templates - Cherevan, Alexey; Gebhardt, Paul; Kunzmann, Andreas; Costa, Ruben D.; Eder, Dominik (ACS Applied Energy Materials, 2018)
Nanostructuring constitutes a promising strategy to increase efficiency and stability of contemporary photocatalysts. Here, we report on the synthesis of highly crystalline Ta2O5 nanotubes (NTs) by using carbon nanotubes (CNTs) as sacrificial hard templates and elucidate the role of residual Fe nanoparticles-often used as catalyst for the CNT growth-on their photocatalytic performance toward H-2 evolution. We show that, when using as grown CNTs, the resulting Ta2O5 NTs contained detectable amounts of Fe and possessed negligible photocatalytic activity. When CNTs were, however, purified from Fe by thermally annealing the CNTs at 2100 degrees C, the same synthetic procedure yielded pure Ta2O5 NTs that showed a 40-fold increase in activity compared to the Fe-containing counterpart. A complementary set of analytical techniques in a combination with additional model experiments indicate that the detrimental effect of the residual Fe on the photocatalytic activity originates from atomic doping and formation of a segregated FeOx phase within the Ta2O5 matrix that can both act as efficient electron traps. Our result highlights that the presence of residual catalyst needs to be taken into account when using CNTs as hard templates and generally illustrates a possible effect of unintentional dopants that are often not considered in preparing functional nanostructures.
CRIS-Team WoS Importer:2019-02-27

Binary Indium-Zinc Oxide Photoanodes for Efficient Dye-Sensitized Solar Cells - Peukert, Wolfgang; Stanzel, Melanie; Kunzmann, Andreas; Guldi, Dirk Michael; Costa Riquelme, Rubén Dario (Advanced Energy Materials, 2016)
The benefits of incorporating binary metal-oxide electrodes en route toward efficient dye-sensitized solar cells (DSSCs) have recently emerged. The current work aims at realizing efficient indium-doped zinc oxide based DSSCs by means of enhancing charge transport processes and reducing recombination rates. Electrochemical impedance spectroscopic assays corroborate that low amounts of indium reduce charge transport resistances and increase electron recombination resistances. The latter are in concert with a remarkable enhancement of the charge collection efficiency from 33% to 83% for devices with ZnO and InZnO photoanodes, respectively. Going beyond 15 mol% of indium, an effective electron trapping increases the charge transport resistance and, in turn, dramatically reduces charge collection efficiency. Upon implementing InZnO into an electron cascade photoanode architecture featuring an InZnO bottom layer and a ZnO top layer, a device efficiency of 5.77% and a significantly high current density of 20.4 mA cm in binary ZnO DSSCs are achieved.
Keywords: binary oxides; charge collection efficiency; flame spray pyrolysis; indium-zinc oxide photoanodes; n-type DSSCs

Choosing the right nanoparticle size-designing novel ZnO electrode architectures for efficient dye-sensitized solar cells - Pfau, Markus; Kunzmann, Andreas; Segets, Doris; Peukert, Wolfgang; Wallace, Gordon G.; Officer, David L.; Clark, Timothy; Costa, Ruben Dario; Guldi, Dirk Michael (Journal of Materials Chemistry A, 2017)
A novel concept for constructing optimized ZnO-based photoanodes as integrative components of dye-sensitized solar cells (DSSCs) is realized by deploying differently sized nanoparticles, ranging from 2 to 10 nm, together with commercially available 20 nm nanoparticles. The 2 nm nanoparticles were used to construct an efficient buffer layer for transparent electrodes based on 10 nm nanoparticles, resulting in a relative increase of device efficiency from 1.8 to 3.0% for devices without and with a buffer layer, respectively. A mixture of 10 and 20 nm nanoparticles was optimized to maximize the diffuse reflection and to minimize the charge transport resistance in a light-scattering layer. This optimization resulted in a homogenous layer of more than 15 mm that provided a device efficiency of 3.3%. The buffer layer, transparent electrode, and light-scattering electrode, were then combined to give an overall efficiency of around 5%. Thus, this work demonstrates that varying the electrode architecture with nanoparticles of different diameters is a powerful strategy for improving the overall efficiency of ZnO-based DSSCs.

Hybrid Dye-Titania Nanoparticles for Superior Low-Temperature Dye-Sensitized Solar Cells - Kunzmann, Andreas; Valero, Silvia; Sepulveda, Angel E.; Rico-Santacruz, Marisa; Lalinde, Elena; Berenguer, Jesus R.; Garcia-Martinez, Javier; Guldi, Dirk Michael; Serrano, Elena; Costa Riquelme, Rubén Dario (Advanced Energy Materials, 2018)
In this work, a new strategy to design low-temperature (≤200 °C) sintered dye-sensitized solar cells (lt-DSSC) is reported to enhance charge collection efficiencies (ηcoll), photoconversion efficiencies (η), and stabilities under continuous operation conditions. Realization of lt-DSSC is enabled by the integration of hybrid nanoparticles based on TiO2-Ru(II) complex (TiO2_Ru_IS)—obtained by in situ bottom-up construction of Ru(II) N3 dye-sensitized titania—into the photoelectrode. Incentives for the use of TiO2_Ru_IS are i) dye stability due to its integration into the TiO2 anatase network and ii) enhanced charge collection yield due to its significant resistance toward electron recombination with electrolytes. It is demonstrated that devices with single-layer photoelectrodes featuring blends of P25 and TiO2_Ru_IS give rise to a 60% ηcoll relative to a 46% ηcoll for devices with P25-based photoelectrodes. Responsible for this trend is a better charge transport and a reduced electron recombination. When using a multilayered photoelectrode architecture with a top layer based only on TiO2_Ru_IS, devices with an even higher ηcoll (74%) featuring a η of around 8.75% and stabilities of 600 h are achieved. This represents the highest values reported for lt-DSSC to date.
CRIS-Team Scopus Importer:2022-04-14
Keywords: charge collection efficiency; dye-sensitized solar cells; hybrid dye-titania nanoparticles; low temperature sintering; multilayered electrodes

Intrinsic and Extrinsic Incorporation of Indium and Single-Walled Carbon Nanotubes for Improved ZnO-Based DSSCs - Schol, Peter; Zhang, Wen Shan; Scharl, Tobias; Kunzmann, Andreas; Peukert, Wolfgang; Schröder, Rasmus R.; Guldi, Dirk Michael (Advanced Energy Materials, 2022)
A common goal in renewable energy research is the production of semiconductor layers with matching additives to gain desirable effects and advantages. Important examples are adjustment of the band gap, enhancing the conductivity, tailoring roughness of the semiconductor, or reducing the recombination rate of charge carriers. In this work a twofold approach is demonstrated. First, the intrinsic incorporation of indium into zinc oxide tunes the band gap of the semiconductor layer of the DSSCs. Second, single-walled carbon nanotubes (SWCNT) as an extrinsic additive improves the charge transport capabilities. To better combine the SWCNTs with the semiconductor layer a protective ZnO shell is grown on the SWCNTs. A combination of current–voltage, incident photon to current efficiency, and electrochemical impedance spectroscopic assays corroborates the positive effects of both additives on the cell performance. The effective charge-carrier diffusion lengths are enhanced from 0.52 µm for pure ZnO to 5.12 µm for low SWCNT concentrations and 15 mol% of indium. This, as well as the increase in collection efficiency from 30.3% to 62.3% enables enhanced transport in these novel devices. A final device utilizing 0.1 wt% SWCNT@ZnO20nm and In15Zn85O yields a current density of 16.49 mA cm−2 and an efficiency of 4.46%.
CRIS-Team Scopus Importer:2022-03-11
Keywords: indium–zinc oxide photoanodes; n-type DSSCs; semiconductor doping; single-wall carbon nanotubes

Molecular insights and concepts to engineer singlet fission energy conversion devices - Casillas, Ruben; Papadopoulos, Ilias; Ullrich, Tobias; Thiel, Dominik; Kunzmann, Andreas; Guldi, Dirk Michael (Energy and Environmental Science, 2020)
In thisReview, we showcase the fundamental processes of intermolecular and intramolecular singlet fission (SF). Furthermore we prioritize the information, which is relevant for the implementation of SF and SF-materials into solar energy conversion devices. We do this, firstly, by referring to the complexity of SF, and discussing key aspects of it; secondly, by mentioning the instrumental efforts, which assisted in unraveling SF in benchmark molecular building blocks such as tetracene, pentacene, and their corresponding dimers/oligomers; thirdly, by presenting a collection of SF-materials, as well as available photophysical and electrochemical data for energy conversion research. Among others, these include perylene-diimides (PDIs), diketopyrrolopyrroles (DPPs), carotenoids, conjugated polymers, and diradicaloids. This Review is rounded off by discussing pioneering contributions of SF in solar energy conversion schemes and highlighting recent developments in the field. Overall, a set of guidelines is given for new directions in SF, that is, the use of new tools to discover new SF-materials (i.e.spectroscopy, computation, machine-learning) and deposition processes (i.e.thin-films, DSSCs, OPVs) to couple SF-materials with the appropriate semiconductors.
CRIS-Team WoS Importer:2020-10-02

N-Heterotriangulene chromophores with 4-pyridyl anchors for dye-sensitized solar cells - Meinhardt, Ute; Lodermeyer, Fabian; Schaub, Tobias; Kunzmann, Andreas; Dral, Pavlo O.; Sale, Anna Chiara; Hampel, Frank; Guldi, Dirk Michael; Costa, Ruben Dario; Kivala, Milan (RSC Advances, 2016)
A series of dimethylmethylene-bridged N-heterotriangulenes decorated with one, two, and three electron-withdrawing 4-pyridyls were synthesized. Their photophysical and electrochemical characteristics were examined and their successful application in n-type TiO2- and ZnO-based dye-sensitized solar cells demonstrated the ability of the 4-pyridyl moiety to act as an anchor.
EAM Import::2019-03-12

Non-Covalent Postfunctionalization of Dye Layers on TiO2 - A Tool for Enhancing Injection in Dye-Sensitized Solar Cells - Luchs, Tobias; Zieleniewska, Anna; Kunzmann, Andreas; Schol, Peter; Guldi, Dirk Michael; Hirsch, Andreas (Chemistry - A European Journal, 2021)
We report on newly tailored dye layers, which were employed, on one hand, for covalent deposition and, on the other hand, for non-covalently post-functionalizing TiO2 nanoparticle films. Our functionalization concept enabled intermixing a stable covalent attachment of a first layer with a highly versatile and reversible hydrogen bonding through the Hamilton receptor-cyanuric acid binding motif as a second layer. Following this concept, we integrated step-by-step a first porphyrin layer and a second porphyrin/BODIPY layer. The individual building blocks and their corresponding combinations were probed with regard to their photophysical properties, and the most promising combinations were implemented in dye-sensitized solar cells (DSSCs). Relative to the first porphyrin layer adding the second porphyrin/BODIPY layers increased the overall DSSC efficiency by up to 43 %.
CRIS-Team WoS Importer:2021-03-12

Porphyrins as Multifunctional Interconnects in Networks of ZnO Nanoparticles and their Application in Dye-Sensitized Solar Cells - Düring, Jasmin; Kunzmann, Andreas; Killian, Manuela; Costa, Ruben Dario; Guldi, Dirk Michael; Gröhn, Franziska (Chemphotochem, 2018)
ZnO nanoparticles of 2.6 to 4.0 nm in size were interconnected by meso-tetra(4-carboxyphenyl)porphyrin (TCPP) for the realization of novel ZnO–TCPP networks, reaching lateral dimensions ranging from 50 to 800 nm. The resulting ZnO–TCPP networks were probed by dynamic light-scattering experiments, transmission electron microscopy, and spectroscopy, and were also tested as photoactive top layers in TiO2 and ZnO dye-sensitized solar cells (DSSCs). Control over these ZnO–TCPP networks on top of the semiconductor electrodes enables efficiency increases of 10 % and 46 % for TiO2- and ZnO-based photoelectrodes, respectively. In other words, effects, such as reducing the electron recombination and increasing the electron lifetime, document the benefits of using tailored functional hybrid systems in DSSCs.
CRIS-Team Scopus Importer:2022-04-14
Keywords: dye-sensitized solar cells; electron transfer; hybrid assemblies; porphyrins; semiconductor nanoparticles

Quaternized Pyridyloxy Phthalocyanines Render Aqueous Electron-Donor Carbon Nanotubes as Unprecedented Supramolecular Materials for Energy Conversion - Anaya-Plaza, Eduardo; Moreno-Oliva, Maria; Kunzmann, Andreas; Romero-Nieto, Carlos; Costa, Ruben Dario; De La Escosura, Andres; Guldi, Dirk Michael; Torres, Tomas (Advanced Functional Materials, 2015)
Exploring new properties in known materials, sometimes even achieving behaviors opposite to those traditionally encountered, is a fundamental aspect of innovation in materials science. In the ﬁeld of energy conversion, for example, the development of water-processed organic solar cells provides environmentally friendlier materials, which contribute to reduce health risks. Herein, a novel approach is described to produce water-soluble electron-donor single wall carbon nanotube (SWCNT) hybrids based on the noncovalent immobilization of quaternized pyridyloxy zinc phthalocyanines (ZnPc) with a varying number of pyridyl substituents. Moreover, the excellent electron-accepting ability of the latter ZnPcs is reported. The introduction of tert-butylphenyl groups at the pyridines enables for the ﬁrst time a complete characterization. The electron-acceptor nature of the ZnPcs enables switching the role of SWCNTs within the resulting supramolecular hybrids. Finally, a proof-of-concept demonstration of the SWCNT/ZnPc hybrids' capacity for energy conversion is presented, paving their way to possible use as active layer material in solar cells processed entirely from aqueous solutions.
EAM Import::2019-03-13

Singlet Fission for Photovoltaics with 130 % Injection Efficiency - Kunzmann, Andreas; Gruber, Marco; Casillas Pacheco, Ruben; Zirzlmeier, Johannes; Stanzel, Melanie; Peukert, Wolfgang; Tykwinski, Rik; Guldi, Dirk Michael (Angewandte Chemie International Edition, 2018)
A novel pentacene dimer (P2) and a structurally analogous monomer (P1) were synthesized for use in n-type dye-sensitized solar cells. In P2, the triplet excited states formed by the rapid, spin-allowed process singlet fission were expected to enable carrier multiplication in comparison to the slow, spin-forbidden intersystem crossing seen in P1. A meta-positioning of the two pentacenes and the carboxylate anchor were chosen in P2 to balance the intramolecular dynamics of singlet fission and electron injection. Electron injection from energetically low-lying triplet excited states of pentacene units necessitated the intrinsic and extrinsic lowering of the Fermi level of the semiconductor. Indium-zinc oxide in the presence of Li+ was found to be the optimum choice for the photoelectrodes. Efficient electron injection from the triplet excited states of P1 and P2 was found, with a carrier multiplication of nearly 130 %.
Keywords: pentacene sensitizers; singlet fission; dye-sensitized solar cells; transient absorption spectroscopy

Singulettspaltung für Photovoltaikanwendungen mit Injektionseffizienzen von bis zu 130 % - Kunzmann, Andreas; Gruber, Marco; Casillas, Ruben; Zirzlmeier, Johannes; Stanzel, Melanie; Peukert, Wolfgang; Tykwinski, Rik R.; Guldi, Dirk Michael (Angewandte Chemie, 2018)

Synergy of Catechol-Functionalized Zinc Oxide Nanorods and Porphyrins in Layer-by-Layer Assemblies - Burger, Alexandra; Kunzmann, Andreas; Costa, Ruben Dario; Srikantharajah, Rubitha; Peukert, Wolfgang; Guldi, Dirk Michael; Hirsch, Andreas (Chemistry - A European Journal, 2018)
Catechol-functionalized, positively charged ZnO nanorods (NRs) and anionic porphyrins were integrated into layer-by-layer (LbL) assemblies. In general, this study focuses on the impact that different porphyrins, varying in size and number of negative charges, exert on the LbL architecture in terms of morphology and spectroscopy. In particular, through a combination of analytical methods, including UV/Vis spectroscopy, SEM, and profilometry, valuable insights into LbL assembly formation were gathered. A key feature was the surface coverage in the resulting films. Denser films and surface coverages were realized when highly negatively charged and sterically demanding porphyrins were employed. As a complement to basic characterization, the LbL assembled films were used to fabricate proof-of-concept solar cells.
Keywords: porphyrins; solar energy conversion; layer-by-layer assemblies; layered compounds; thin films; ZnO nanorods

Thin membranes versus bulk substrates: Investigation of proximity effects in focused electron beam-induced processing - Walz, Marie-Madeleine; Vollnhals, Florian; Rietzler, Florian; Schirmer, Michael; Kunzmann, Andreas; Steinrück, Hans-Peter; Marbach, Hubertus (Journal of Physics D-Applied Physics, 2012)
The resolution of focused electron beam induced processing techniques is limited by electron scattering processes. General wisdom holds that using a membrane, this can be effectively improved due to a cutoff of the electron interaction volume and thus diminished proximity effects. Recently, we demonstrated that in contrast to the expectation, proximity effects can be indeed larger on a 200nm silicon nitride membrane than on the respective bulk substrate, due to charging-induced surface activation. Herein, we expand these investigations on proximity effects in electron beam-induced surface activation to other substrates and to electron beam-induced deposition followed by autocatalytic growth. © 2012 IOP Publishing Ltd.

Tuning pentacene based dye-sensitized solar cells - Kunzmann, Andreas; Gruber, Marco; Casillas, Ruben; Tykwinski, Rik; Costa, Ruben Dario; Guldi, Dirk Michael (Nanoscale, 2018)